Preservice teachers’ perceptions of large-scale instructional units in mathematics education - Xu, Jiawen; Zhou, Ying; Pang, Guoping (Pi Radian: Journal of Mathematics Education, 2025)
While Large-Scale Instructional Units in Mathematics Education benefit students’ core competencies, in-service teachers’ professional capabilities, and preservice teachers’ higher-order thinking, research on this construct remains scarce. Most preservice and in-service teachers lack in-depth understanding of these units, with some unaware underscoring the urgency of investigating Preservice Teachers’ Perceptions of Large-Scale Instructional Units in Mathematics Education, as such perceptions shape the units’ classroom implementation. This study explores preservice mathematics teachers’ perceptions of these units via a questionnaire survey, with participants from over ten universities (e.g., Guangxi Normal University, Chongqing Normal University). Using data from more than 400 valid questionnaires, it identifies their knowledge levels and internal recognition of the units, analyzes their views on the units’ learning and practical value, and synthesizes strategies for learning and disseminating the units. Key findings reveal 69% of the preservice teachers have limited knowledge of the units, while over 95% recognize their learning value. Ultimately, this study fills the research gap, strengthens their awareness of the units, and provides empirical references for subsequent mathematics teaching practices.